Konsep Maslahat Dalam Penetapan Hukum Islam (Telaah Kritis Pemikiran Hukum Islam Najamuddin At-Thufi) - Amri, Miftahul (Universitas Trunojoyo Madura, 2018)
In Islamic legal thinking when it is associated with social change so it has two theories, they are the theory of immortality and the theory of adabtabilitas. Based on the theory, Islamic legal thinking is developing now more than has tendency to follow the pattern of adaptability theory that is Islamic law as a law created by God for the humanity, and can adapt to the development of the times, so that he can be changed in order to realize in benefit of human being generally (maslahat al-ummah). Among of many mufties who follow the theory of adaptability, is Najamuddin Al-Thufi. The basic framework theory of adaptability is the principle of maslahat, which is a fundamental value for the sustainability of Islamic law in the concept of social change in decision of Islamic law. This written is a criticizes the concept of maslahat at-thufi which applies not only to the issue of law which nash is nothing , but also applies to the context which nash is exist as like in the matter of mu'amalah. When analyzed carefully, this concept can allow for a conflict between nash and maslahat, and the application of this concept afraided will apply to follow the passion and justify the haram tobe halal by on the pretext of maslahat.